Restorative Justice in Application for Crime Investigation on Property - Ragil Tri Wibowo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Restorative Justice or mediating a settlement out of court or in the absence of legal proceedings, a form of means to enforce the laws that promote justice for those who were litigants. In addition there is the meaning contained in the Restorative Justice or settlement out of court legal settlement that is the rapid acceleration by not leaving the rights of each party and in accordance with the laws of life (living law) which is part of the customs that exist in Indonesian society. However Restorative Justice and mediation in Indonesia there is no definite legal umbrella so that the rule of law has not regulated the process of implementation, but reality on the ground Restorative Justice or mediation process has been commonly carried out and have a positive impact. In the most preferred law enforcement is a sense of justice both the victim and of the perpetrator so that mediation between the parties is very influential in the settlement. In the implementation of Restorative Justice and mediation can only be carried out against the legal process done by children as offenders (minors) with Diversi term, but for other general criminal cases there are no rules that govern them. Restorative Justice and mediation have often carried out in developed countries, but in Indonesia there is no definite rules related to the implementation, therefore we are pushing for the parties berkompenten about the manufacture or preparation of regulations on the enforcement of the failure by a review of the application of Restorative Justice in common criminal case.Keywords: Investigation; The Law Of Life; Restorative Justice.